Conselhos locais de saúde : caminhos e (des)caminhos da participação social no Sistema Único de Saúde - Lisboa, Edgar Andrade (2014)
From decentralization, new instances and new alternative trading system of the organizational structure of the Sistema Único de Saúde (SUS) was created. Among these alternatives, we can mention the health councils, important channels for social participation. However, due to the limitations of these traditional channels of articulation between state and society, include the ideals of participatory management and Local Health Boards (LHB) as an alternative for renewal and creation of more flexible, porous and effective to complex social demands instances. In this sense, we analyze the process of creation and implementation of CLS in the municipality of Anchieta/ES, from a quali-quantitative approach. Initially, we trace the socioeconomic and political profile of the elected councilors, from a questionnaire administered to a sample of 54 counselors, data were categorized and analyzed through the use of descriptive statistics. Then interviewed thirteen directors, two separate councils of the city, proceeding to an analysis of the material from the ideals of Bardin (2000). The results showed that councils were created at the initiative of the municipal administration in 2011 , and that simply institutionalize them as a space for social participation was not sufficient to promote social mobilization and community involvement. Regarding the profile of local councilors, 78 % are women, predominantly white race / color, age between 20 and 39 years and public employees, 57% have high school and participated as a counselor for two years, and 60 % of these had already other experiences similar to CLS participation. The material from the interviews, four categories emerged from the analysis, namely: 1) To be or not to be health counselor? That is the question; 2) not belonging and non-participation; 3) Local Health Councils: links, media and mediations; 4) The exogeny administration and obstacles to social participation. Barriers to the functioning of boards of health, even at the local level are still challenges to be overcome, so that these instances are more influential in public administration, according to the principles of its creation. Social participation and democracy are fundamental to the construction of health policies which meet the demands of the community. However, to ensure democracy in society not just promote decentralization. It is necessary that political subjects resist the relations of domination, oppression and subordination. For this, it is essential education programs for citizens of those involved to participate in these forums. What motivates us, in short, is to note the existence, among the elected councilors, of subjects protagonists of their own becoming; subjects that act as agents, motivators dreams and projects for the sake of public health and their community.